2023
DOI: 10.1039/d3sc02924g
|View full text |Cite
|
Sign up to set email alerts
|

Electron delocalization of robust high-nuclear bismuth-oxo clusters for promoted CO2electroreduction

Baoshan Hou,
Haiyan Zheng,
Kunhao Zhang
et al.

Abstract: A family of calix[8]arene-protected bismuth-oxo clusters from Bi4 to Bi40Mo2 was prepared. And BiOC-5 showed excellent performance for CO2 → HCOOH conversion with a faradaic efficiency of 97% at −0.95 V vs. RHE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Compared with W 18 O 49 @ZIF-8, the smaller EIS value of Cu–W 18 O 49 @ZIF-8 indicates an advantage for electronic transfer. 66–69 Meanwhile, the high density of electrocatalytic active sites resulting from the multi-porosity structure should also contribute to the high yield of urea.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with W 18 O 49 @ZIF-8, the smaller EIS value of Cu–W 18 O 49 @ZIF-8 indicates an advantage for electronic transfer. 66–69 Meanwhile, the high density of electrocatalytic active sites resulting from the multi-porosity structure should also contribute to the high yield of urea.…”
Section: Resultsmentioning
confidence: 99%
“…The more delocalized electrons, the stronger the electrical conductivity. Indeed, extensive studies have recently revealed the importance of electron delocalization in tailoring the local properties of solid materials and endowing them with new functionalities and/or enhanced performances. Particularly, the control of electron delocalization in semiconductor materials can reduce the highest occupied molecular orbital–lowest unoccupied molecular orbital (HOMO–LUMO) energy level difference, which is beneficial for improving the initial charge transfer and separation, facilitating their electrical conductivity, charge-carrier mobilities, and optical properties. , Thus, the rational creation of local electron delocalization may pave the way to tune and optimize the performance. Taking into account the subtle influence of electron delocalization on properties, especially photocatalysis, it is necessary to find a suitable model with tunable delocalized electrons for a deeper understanding of the relationship between the local electron-delocalization control and the factors affecting performance at a molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 This review discusses that CO 2 RR can be influenced by the delocalization states of the catalysts from the following aspects: (1) maintaining the stability of catalysts during CO 2 RR. 23 It is well known that the CO 2 reaction potential is a reduction potential. Under an overpotential, the catalyst is likely to be reduced if the reaction is prolonged.…”
Section: Introductionmentioning
confidence: 99%